Serial transverse enteroplasty to facilitate enteral autonomy in selected children with short bowel syndrome. Issue 10 (14th July 2014) - Wester, T.; Borg, H.; Naji, H.; Stenström, P.; Westbacke, G.; Lilja, H. E.
<x xml:space="preserve">Abstract</x> Background Serial transverse enteroplasty (STEP) was first described in 2003 as a method for lengthening and tapering of the bowel in short bowel syndrome. The aim of this multicentre study was to review the outcome of a Swedish cohort of children who underwent STEP. Methods All children who had a STEP procedure at one of the four centres of paediatric surgery in Sweden between September 2005 and January 2013 were included in this observational cohort study. Demographic details, and data from the time of STEP and at follow‐up were collected from the case records and analysed. Results Twelve patients had a total of 16 STEP procedures; four children underwent a second STEP. The first STEP was performed at a median age of 5·8 (range 0·9–19·0) months. There was no death at a median follow‐up of 37·2 (range 3·0–87·5) months and no child had small bowel transplantation. Seven of the 12 children were weaned from parenteral nutrition at a median of 19·5 (range 2·3–42·9) months after STEP. Conclusion STEP is a useful procedure for selected patients with short bowel syndrome and seems to facilitate weaning from parenteral nutrition. At mid‐term follow‐up a majority of the children had achieved enteral autonomy. The study is limited by the small sample size and lack of a control group.